Statin use and risk of cataract: A nested case-control study within a healthcare database. (August 2016) - Casula, Manuela; Soranna, Davide; Corrao, Giovanni; Merlino, Luca; Catapano, Alberico Luigi; Tragni, Elena
Abstract: Background and aims: We aimed to assess the association between exposure to statins and hospitalization for cataract. Methods: A population-based, nested case-control study was performed on a cohort of 134, 441 patients from Lombardy (Italy), newly treated with statins between 2005 and 2007. Cases were patients hospitalized for cataract or lens extraction surgery after initial statin prescription until December 31, 2012. For each case patient, up to 5 controls were randomly selected from the cohort and matched by gender, age at cohort entry, and date of index prescription. Logistic regression was used to model the outcome risk associated with low (proportion of days covered, PDC 25–49%), intermediate (PDC 50–74%), and high (PDC ≥ 75%) adherence compared with very-low adherence (PDC < 25%). Results: 1334 case patients were matched to 6601 controls. Mean age (SD) of cases and controls was about 70 years (9 years) and 51% of them were men. There was a slight but continuous trend toward an increased risk of cataract as adherence to statin therapy increased in the adjusted risk models, with a significant odds ratio of 1.19 (95% CI 1.01–1.40%) for PDC 50–74% and 1.20 (95% CI 1.02–1.40) for PDC ≥ 75% vs . PDC < 25%, respectively. There was no statistical evidence that the effect of statins on cataract risk differed according to statin potency at starting therapy. Conclusions: Statin therapy was associated with a modestly increased risk of cataract surgery. Nevertheless, in view of the overwhelming benefit of statins for reduction of CV events, clinical practice for statins therapy does not need to change. Highlights: The influence of statin therapy on the development of cataracts in the general population is still debated. We observed a slight but continuous trend toward an increased risk of cataract as adherence to statin therapy increased. In view of the overwhelming benefit of statins for reduction of CV events, clinical practice for statins therapy does not need to change.